Associations Between Genotype and Peripheral Complement Proteins in First-Episode Psychosis: Evidences From C3 and C4 - Chen, Yu; Zhao, Zhenguo; Lin, Fen; Wang, Lifang; Lin, Zheng; Yue, Weihua (Frontiers in Genetics, 2021)
Schizophrenia is a common neuropsychiatric disorder with complex pathophysiology. Recent reports suggested that complement system alterations contributed to pathological synapse elimination that was associated with psychiatric symptoms in schizophrenia. Complement component 3 (C3) and complement component 4 (C4) play central roles in complement cascades. In this study, we compared peripheral C3 and C4 protein levels between first-episode psychosis (FEP) and healthy control (HC). Then we explored whether single nucleotide polymorphisms (SNPs) at C3 or C4 genes affect peripheral C3 or C4 protein levels. In total, 181 FEPs and 204 HCs were recruited after providing written informed consent. We measured serum C3 and C4 protein levels using turbidimetric inhibition immunoassay and genotyped C3 and C4 polymorphisms using the Sequenom MassArray genotyping. Our results showed that three SNPs were nominally associated with schizophrenia (rs11569562/C3: A > G, p = 0.048; rs2277983/C3: A > G, p = 0.040; rs149898426/C4: G > A, p = 0.012); one haplotype was nominally associated with schizophrenia, constructed by rs11569562–rs2277983–rs1389623 (GGG, p = 0.048); FEP had higher serum C3 and C4 (both p < 0.001) levels than HC; rs1389623 polymorphisms were associated with elevated C3 levels in our meta-analysis (standard mean difference, 0.50; 95% confidence interval, 0.30 to 0.71); the FEP with CG genotype of rs149898426 had higher C4 levels than that with GG genotypes (p = 0.005). Overall, these findings indicated that complement system altered in FEP and rs149898426 of C4 gene represented a genetic risk marker for schizophrenia likely through mediating complement system. Further studies with larger sample sizes needs to be validated.